PENGEMBANGAN MULTIMEDIA BERBANTUAN GAME EDUKASI DIGITAL PADA MATERI KERAGAMAN BUDAYA JAWA TIMUR UNTUK MENINGKATKAN HASIL BELAJAR KELAS IV SDN BURENGAN 1 - Segti Nur Septiani; Karimatus Saidah; Wahid Ibnu Zaman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research and development aims to determine the validity, practicality, and effectiveness of the Digital Educational Game on the Material of East Java Cultural Diversity to Improve Learning Outcomes of Class IV SDN Burengan 1. This study uses a research and development method with the ADDIE model consisting of 5 stages, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The subjects of this study were teachers and 28 students of class IV SDN Burengan 1. The results of this study indicate that (1) The results of the validity test obtained a material expert score of 96% and a media expert score of 90%. The average value of the validity results is 93% with very valid criteria. (2) The results of the teacher's practicality test were 82% and the student response score was 90%. From these two values, a percentage of 86% can be accumulated with practical criteria. (3) The results of the educational game effectiveness test obtained an average pretest score of 66.25%. Then, the average posttest score was 89.25%, this score has met the KKTP with effective criteria. It can be concluded that the Digital Educational Game on the Material of East Javanese Cultural Diversity is stated to be very valid, very practical, and effective in improving student learning outcomes on the material of East Javanese cultural diversity.